Pengaruh Store Atmosphere Dan Harga Terhadap Keputusan Pembelian Konsumen Pada Toko Adin Di Kota Ambon - Wa Santi; Harold Hursepuny; Marie Ch Tahalele (Jurnal Administrasi Terapan, 2024)
This study aims to analyze the influence of store atmosphere and price on consumer purchasing decisions at Adin Store in Ambon City. Adin Store has experienced various issues that reduce consumer comfort and satisfaction, such as difficult access, uncomfortable interiors, inefficient layout, and negative perceptions of prices. These factors have resulted in a decline in the store's customer base. A sample of 60 respondents was taken using a non-probability sampling technique with an accidental sampling approach. Data were collected using a survey method by distributing questionnaires to consumers. The analytical method used is multiple linear regression analysis with the help of SPSS 24.0 software. The results of the study show that the first hypothesis produced a t-value of 4.903 with a probability of 0.030 (p < 0.05), indicating that store atmosphere has a positive and significant effect on purchasing decisions at Toko Adin in Ambon City. The second hypothesis produced a t-value of 5.863 with a probability of 0.000 (p < 0.05), indicating that price also has a positive and significant effect on purchasing decisions. price was found to have a greater influence on purchasing decisions compared to store atmosphere at Toko Adin in Ambon City. Keywords: Store Atmosphere, Price, Purchasing Decision.